Novel approach to supercritical fluid chromatography-mass spectrometry analysis of metal ions using EDTA complexation - Plachká, Kateřina; Bredendiek, Felix; Nováková, Lucie; Parr, Maria Kristina (Analytica chimica acta, 2023)
BACKGROUND: Reliable methods enabling detection of metal ions, and especially heavy metals, in different matrices are necessary in various fields such as ecology, pharmaceuticals and toxicology. As some of the currently used methods suffer from spectral and chemical interferences, this study investigates the applicability of SFC-MS/MS for the determination of metal ions. RESULTS: Effective novel approaches for metal ion analysis using CO2-based mobile phase were developed using three ligands forming metal complexes. As metal-EDTA complexes are prepared by simple addition of EDTA to the solution containing metal ions, this approach to metal ion analysis does not require laborious synthesis and isolation of solid metal-complexes. Besides, two other approaches using diethyldithiocarbamate and acetylacetonate as ligands were compared. Metal complexes of Cu, Co, Cr, Fe, Al, Mn, and Zn with all 3 ligands were synthesized and their identity was confirmed by high-resolution mass spectrometry (HRMS). The suitability of the three developed UHPSFC-MS/MS methods was examined using the determination of calibration range and repeatability of injections. Moreover, the universality of the developed UHPSFC-MS/MS method for the determination of metal-EDTA complexes was proved by analyzing Ni, Bi and Pb as additional metal ions. SIGNIFICANCE AND NOVELTY: This study demonstrates the extended range of applicability for SFC based separations. For the first time, the possibility to analyze metal complexes with EDTA using a fast and reliable ultra-high performance supercritical fluid chromatography-tandem mass spectrometry (UHPSFC-MS/MS) method is reported. The three developed UHPSFC-MS/MS methods are able to separate DDC, acac, and EDTA complexes of various metals very efficiently (total cycle times of 5, 2, and 3 min, respectively). They offer a fast and green alternative to chromatographic methods commonly used for metal ion analysis.
Keywords: Supercritical fluid chromatography; Mass spectrometry; EDTA; Acetylacetonate; Metal ion complexes; Diethyldithiocarbamate